Romantic “Forges of Nature” from the Ecocritical Perspective - Hamerski, Wojciech (Porównania, 2021)
The article proposes an ecocritical approach to Polish Romanticism. Both British and American “green studies” are deeply rooted in the literature of the 19th century: Wordsworth, Clare, Shelley, Thoreau, Emerson and Melville serve as a significant point of reference for contemporary critics. The article argues that the “national trauma” of the Partitions considered as an major obstacle for ecocritical reading of Polish Romantic literature creates an opportunity to establish a new idiom in “green studies”.